Influence of Implant Connection Type on the Biomechanical Environment of Immediately Placed Implants - CT-Based Nonlinear, Three-Dimensional Finite Element Analysis - Pessoa, Roberto S. [UNESP]; Muraru, Luiza; Marcantonio, Elcio [UNESP]; Vaz, Luis Geraldo [UNESP]; Sloten, Jos Vander; Duyck, Joke; Jaecques, Siegfried V. N. (Wiley-Blackwell, 2010)
Purpose:The purpose of the present study was to evaluate the biomechanical environment of immediately placed implants, before and after osseointegration, by comparing three different implant-abutment connection types.Materials and Methods:A computer tomography-based finite element model of an upper central incisor extraction socket was constructed containing implants with either external hex, internal hex, or Morse-taper connection. Frictional contact elements were used in the bone, implant, abutment, and abutment screw interfaces in the immediately placed simulations. In osseointegrated simulations, the repair of bone alveolar defect and a glued bone-to-implant interface were assumed. By analysis of variance, the influence was assessed of connection type, clinical situation, and loading magnitude on the peak equivalent strain in the bone, peak von Mises stress in the abutment screw, bone-to-implant relative displacement, and abutment gap.Results:The loading magnitudes had a significant contribution, regardless of the assessed variable. However, the critical clinical situation of an immediately placed implant itself was the main factor affecting the peak equivalent strain in the bone and bone-to-implant displacement. The largest influence of the connection type in this protocol was seen on the peak equivalent stress in the abutment screw. on the other hand, a higher influence of the various connection types on bone stress/strain could be noted in osseointegrated simulations.Conclusions:The implant-abutment connection design did not significantly influence the biomechanical environment of immediately placed implants. Avoiding implant overloading and ensuring a sufficient initial intraosseous stability are the most relevant parameters for the promotion of a safe biomechanical environment in this protocol.
Keywords: finite element analysis; immediate implant loading; immediate implant placement